Endoscopic anatomical study of the trans-lateral molar approach to the infratemporal fossa - Cai, Wei-wei; Zou, Yan; Kang, Zhuang; Liang, Jian-gang; He, Hai-yong; Yang, Qin-tai (European archives of oto-rhino-laryngology, 2019)
Background The infratemporal fossa (ITF) is located deep in the skull base. Recently, the endoscopic transoral approach has enabled maxillofacial surgeons to access the ITF using a less invasive approach compared to the traditional transfacial and endonasal endoscopic approaches. Objective The present study aims to provide maxillofacial surgeons with new data concerning direct endoscopic measurement and precise anatomical topography features of the endoscopic trans-lateral molar approach to ITF by comparing the endoscopic and regional anatomy of ITF. A clinical case receiving the proposed surgical approach is used to determine the feasibility of this technique. Method The anatomical data were obtained by measuring the bone anatomical landmarks and analyzing the CT imaging data using GE’s Advance Windows 4.1 software on 25 subjects (50 sides). Morphological pictures of the regional anatomy and endoscopic anatomy were obtained from 6 (12 sides) adult cadaver heads, and the anatomical features were described. The present study reports the management of one case using the proposed surgical approach. Results The proposed surgical approach clearly revealed neurovascular, muscular, and surgical landmarks in the ITF. The surgical case supports the minimally invasive treatment approach, which could rapidly access the ITF and completely excise benign tumors. Conclusion The anatomical studies and surgical case presentation helps us understand the spatial relationship of surgical landmarks of the surgical approach to the ITF for the treatment of benign lesions in the deep cranial base area.